2020
DOI: 10.17130/ijmeb.853414
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Economic Growth and Capacity for Generating Co2 Emissions: Testing the Validity of the Environmental Kuznets Curve for Turkey

Abstract: This study is an attempt to measure the validity of the inverted U-shaped Environmental Kuznets Curve through empirical treatment with the help of ARDL bound test and vector error correction model. The study then aims to find whether there is a long-term relationship between economic growth and environmental pollution. In the literature, the methodology is used by different researchers for different countries. The findings, in general, endorse the presence of inverted U association between growth of the econom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…Besides this, regardless of the cointegration, many studies specific to the Monte Carlo simulation have demonstrated that RB method performs excellently over standard asymptotic testing. Also, studies 4348 proved that even in a small sample, the corrected LR tests could potentially present a better size, and enhanced power characteristics. The research results reveal that, without the factor of cointegration, all the standard tests which are not associated with the RB method, are unable to function adequately, especially in smaller sample sizes.…”
Section: Model and Methodologymentioning
confidence: 99%
“…Besides this, regardless of the cointegration, many studies specific to the Monte Carlo simulation have demonstrated that RB method performs excellently over standard asymptotic testing. Also, studies 4348 proved that even in a small sample, the corrected LR tests could potentially present a better size, and enhanced power characteristics. The research results reveal that, without the factor of cointegration, all the standard tests which are not associated with the RB method, are unable to function adequately, especially in smaller sample sizes.…”
Section: Model and Methodologymentioning
confidence: 99%